Appendicular sliding in right inguinal hernia - Croci, Fabio; Gastambide, Carmelo; Terra, Eneas; Cordal, Adriana (Cirugía del Uruguay, 1984)
Authors dlscuss hernlal pathology as determlned by appendlcular dlsplacement In rlght lngulnal hernias, havlng found that the lncldence of thls fact Is very low. AII cases found occurred In men. In 89% of cases, ap• pendectomy was carrled out wlthout compllcatlons